Rethinking the History of Democracy in Spain - Herrera , Antonio; Acosta, Francisco (Routledge/Canada Blanch Studies on Contemporary Spain, 2024)
Focusing on the processes of political socialisation and democratisation that took place in Spain during the nineteenth and twentieth centuries, this book brings together specialists who propose the need to rethink the contemporary history of democracy in Spain to build a new narrative. To do so, the authors go down to the local level, where they are able to trace a political culture that forged the foundations of a process of political ""modernization"" much more complex than what conventional historiography has conveyed, even though it was not always transferred institutionally to the national level. The idea of a rural Spain that was backward, apolitical, violent and unprepared for democracy gives way to a more interesting history which, while recognising the peculiarities of the country and the important limitations to democracy, shows examples that could help build a new narrative closer those of other neighbouring countries. Aimed at contemporary historians interested in Spain and Europe, the book also addresses the debates faced by other social scientists on the concept of democracy. This dialogue between history, sociology and political science is particularly present in a special final chapter featuring a discussion of democracy and its application to Spanish history.